The effect of inclusive leadership on team innovation with team voice as a mediation variable at pt selamat jaya, kabupaten bengkulu utara - Finarti, Finarti; Sulastri, Sulastri (Human Resource Management Studies, 2023)
This study aims to analyze the effect of inclusionsive leadership on team innovation with team voice as a mediating variable at PT Selamat Jaya Kabupaten Bengkulu Utara. The population of this research is all employees PT Selamat Jaya Kabupaten Bengkulu Utara is 215 employee. The number of samples in this study is 140 employees using technology clusters proportional random sampling. The research design used in this study is causative research. The data analysis technique used is the Structural Equational Model (SEM) with the help of SmartPLS 3.3. The results of this study indicate that: (1)there is a direct and significant influence between inclusive leadership and the innovation team.(2)there is a direct and significant influence between inclusive leadership and team voice. (3)there is a direct and significant effect between team voice with team innovation. (4)there is a positive and significant indirect (mediation) effect between inclusive leadership on team innovation through team voice as a mediating variable.